STRATEGI PENGEMBANGAN KEMITRAAN TERNAK AYAM BROILER PT. XYZ - Latifa Hanum; Bunasor Sanim; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2011)
The objectives of this research are to (1) analyze profit and BEP of plasma farmers (2) analyze internal and external strategic factors that influence development of broiler partnership in PT. XYZ, (3) formulate the alternative strategies of broiler partnership in PT. XYZ, (4) formulate selected priority strategy to develop broiler partnership in PT. XYZ. This research uses descriptive method based on case study on broiler partnership in PT. XYZ. Based on BEP analysis, BEP (production) of plasma farmers is in the range 79,91%-86,58% from chick-in capacity, and BEP (price) is in the range of Rp 11.684 – Rp 12.191 per chicken on market price. PT. XYZ partnership’s position in IE matric was second quadrant (grow and builds). The results of SWOT analysis are: a) vertical integration strategy through feedmill, breeding and chicken slaughterhouse, b) improving production capacity through capacity building of plasma farmers, c) improvement in bio-security aspects of maintenance, and d) improving the quality of technical staff and improving supervision. The priority strategy from QSPM analysis is improving production capacity through capacity building of plasma farmers. The strategy to improve production capacity can be done by maximize or add their capacity, and add the new plasma farmers. Keywords: Broiler Partnership, Internal Environment, External Environment, Internal-external, Improvement Priority